Automated Design of Reconfiguration Strategies Increases Reliability - Lurye, Oleg; Kromov, Ivan; Trächtler, Ansgar (Proceedings of Reliability, Avaliability and Maintainability Symposium)

Fahrerassistenzsystem für energie- und zeitoptimales Fahren durch prädiktive Geschwindigkeitsprofil-Planung - Gausemeier, Sandra; Trächtler, Ansgar; Jäker, Karl-Peter (13. Braunschweiger Symposium AAET)

Using Algorithmic Differentiation for the Multiobjective Optimization of a Test Vehicle - Ringkamp, Maik; Walther, Andrea; Reinold, Peter; Witting, Katrin; Dellnitz, Michael; Trächtler, Ansgar (EVOLVE)

Erhöhung der Verlässlichkeit eines innovativen Versuchsfahrzeugs mit Einzelradaktorik durch Rekonfiguration der Regelung - Lurye, Oleg; Trächtler, Ansgar (13. Braunschweiger Symposium AAET)

Cooperative transportation of a load using nonholonomic mobile robots - Loh, Chia Choon; Trächtler, Ansgar (Procedia Engineering)

Modellbasierter Entwurf zweier kooperierender Delta-Roboter - Teichrieb, Heinrich; Just, Viktor; Dziwok, Stefan; Pohlmann, Uwe; Schierbaum, Thomas; Trächtler, Ansgar (Berichtsband des Tag des Systems Engineering 2012)

Constrained Linear Quadratic Optimal Controller for Motion Control of ATMOS Driving Simulator - Al Qaisi, Imad; Trächtler, Ansgar (Driving Simulation Conference 2012 Europe - DSC 2012)

Multi-robot Approach for Automation of an Industrial Profile Lamination Process - Bielawny, Dirk; Bruns, Torsten; Loh, Chia Choon; Trächtler, Ansgar (2012 International Symposium on Robotics and Intelligent Sensors (IRIS))

A self-correcting Approach for the Bending of Metal Parts - Damerow, Ulf-Hendrik; Borsig, Michael; Homberg, Werner; Trächtler, Ansgar (Key Engineering Materials Vols. 504-506 (2012))

Cascaded Heterogeneous Simulations for Analysis of Mechatronic Systems in Large Scale Transportation Scenarios - Hassan, Bassem; Wassmann, Helene; Klaas, Alexander; Kessler, Jan Henning (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference)

Model-based Design of Self-Correcting Strategy for a Punch Bending Machine - Borsig, Michael; Trächtler, Ansgar; Damerow, Ulf-Hendrik; Homberg, Werner (14th IFAC Symposium on Information Control Problems in Manufacturing, INCOM 2012)

Human in the Loop: Optimal Control of Driving Simulators and New Motion Quality Criterion - Al Qaisi, Imad; Trächtler, Ansgar (IEEE International Conference on Systems, Man and Cybernetics - IEEE SMC 2012)

Analyzing Product Lifecycle Costs for a Better Understanding of Cost Drivers in Additve Manufacturing - Lindemann, C.; Jahnke, U.; Moi, M.; Koch, R. (23rd Annual International Solid Freeform Fabrication Symposium)
The costs of additive manufactured parts often seem too high in comparison to those of traditionally manufactured parts, as the information about major cost drivers, especially for additive manufactured metal parts, is weak. Therefore, a lifecycle analysis of additive manufactured parts is needed to understand and rate the cost drivers that act as the largest contributors to unit costs, and to provide a focus for future cost reduction activities for the Additive Manufacturing (AM) technology. A better understanding of the cost structure will help to compare the AM costs with the opportunity costs of the classical manufacturing technologies and will make it easier to justify the use of AM manufactured parts. This paper will present work in progress and methodology based on a sample investigated with business process analysis / simulation and activity based costing. In addition, cost drivers associated with metal AM process will be rated.

The MoSGrid Community From National to International Scale - Gesing, Sandra; Herres-Pawlis, Sonja; Birkenheuer, Georg; Brinkmann, André; Grunzke, Richard; Kacsuk, Peter; Kohlbacher, Oliver; Kozlovszky, Miklos; Krüger, Jens; Müller-Pfefferkorn, Ralph; Schäfer, Patrick; Steinke, Thomas (Proc. EGI Community Forum)

STIR: Software for Tomographic Image Reconstruction Release 2 - Thielemans, Kris; Tsoumpas, Charalampos; Mustafovic, Sanida; Beisel, Tobias; Aguiar, Pablo; Dikaios, Nikolaos; W Jacobson, Matthew (Physics in Medicine and Biology)

Parallel algorithm for computation of second-order sequential best rotations - Redif, Soydan; Kasap, Server (Int. Journal of Electronics)

Parallel Processor Design and Implementation for Molecular Dynamics Simulations on a FPGA Parallel Computer - Kasap, Server; Benkrid, Khaled (Journal of Computers)

Evaluierung medizinischer Volumenrendering-Algorithmen durch empirische Studien - Domik, Gitta; Arens, Stephan; Tünnermann, Jan; Scharlau, Ingrid Rose (FIfF-Kommunikation)
Keywords: Informatik; Visualisierung; Psychologie; Experimentaldesign

Introducing Google Chart Tools and Google Maps API in Data Visualization Courses - Zhu, Y. (IEEE Computer Graphics and Applications)

Teaching 3D Computer Animation to Illustrators: The Instructor as Translator and Technical Director - Koning, W. F. (IEEE Computer Graphics and Applications)